Teachers’ Roles in AI-Integrated Gamified Learning Environments to Enhance Creativity and Students’ Critical Thinking - Hendarman Hendarman; Dian Sudiantini; Mayadi Mayadi; Mira Mirnawati; Lisa Chandrasari Desianti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study examines the role of teachers in designing and implementing AI-integrated gamified learning environments to enhance teacher creativity and students’ critical thinking skills at the senior high school level. Grounded in the demands of 21st-century education, this research responds to persistent challenges in classroom practice, including low student motivation, limited literacy skills, and passive learning engagement. Employing a qualitative case study approach, data were collected through in-depth interviews with 30 teachers, supported by analysis of student learning instruments. Thematic analysis was used to identify patterns related to teachers’ pedagogical creativity, instructional decision-making, and classroom interactions. The findings suggest that teachers play a crucial role in transforming gamification from a technical tool into a meaningful pedagogical strategy by creatively integrating AI-supported features, such as personalized feedback, adaptive learning pathways, and smart tutoring assistance. Teachers reported that this approach increased students’ learning motivation, engagement, and ability to critically analyze and understand concepts. However, the study also reveals challenges faced by teachers, including variations in student readiness, low literacy levels, and students’ overreliance on technological support without deep reflection. The study concludes that the effectiveness of gamified learning environments depends largely on teachers’ creative and reflective pedagogical practices, particularly when supported by AI-driven personalization. These findings underscore the strategic role of teachers as key agents of innovation and contribute to the development of teacher-centered, technology-enhanced learning models that aim to strengthen creativity and critical thinking skills in Indonesian secondary education.